Meningkatan Hasil Belajar Service Bawah Dalam Permainan Bola Voli Melalui Permainan Bolkendi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
This study aims to improve the learning process through bolkendi game service in order to improve learning outcomes for the volleyball game. The research method used was Classroom Action Research. The subject of this research is on a Class IV student Delegtukang Public Elementary School District of Pekalongan Wiradesa 2013/2014academic year with 28 students. Data analysis was performed by descriptive comparative aimed to compare the before and after a study conducted remedial action. From the research conducted, an increase in student learning outcomes from the initial condition to cycle 1 and cycle 2cycle average value of 1 (71.99) and the average cycle 2 (81.46), so that an increase of the initial conditions to cycle 2 is (9.47). Increased movement to the service learning volleyball can be seen from the KKM (73), after the action in cycle 1students who pass the values learned as many as 16 of the 28 students (57.14%) and in cycle 2 which has a value of as much as 28 above KKM of 28 or completion of(100%). The conclusion of this study is the use of games can improve learning outcomes bolkendi service under volleyball game for the fourth-grade students of State Elementary School Delegtukang Wiradesa Pekalongan District of academic year 2013/2014